Toxicity of co-exposure of microplastics and lead in African catfish (Clarias gariepinus) - Soliman, Hamdy A. M.; Salaah, Sally M.; Hamed, Mohamed; Sayed, Alaa El-Din H. (Frontiers in Veterinary Science, 2023)
Microplastics (MPs) are an emerging threat to freshwater ecosystem with several ecotoxicological ramifications for fish. Microplastics (MPs) can adsorb heavy metals on their surfaces and increase their availability to aquatic organisms. The combined impact of lead and microplastics on fish has only been studied seldom utilising a variety of markers. The present study aimed to evaluate the hematological, biochemical, and inflammatory signals (cytokines), as well as antioxidant enzymes in African catfish (Clarias gariepinus) exposed to lead (Pb) and MPs individually and combined for 15 days (acute toxicity experiment). The fish were split into four groups, the first of which was the control group. The second group received exposure to 1 mg/L of lead nitrate (Pb(NO3) 2 ). The third group was given 100 mg/L of MPs. A solution containing 100 mg/L of MPs and 1 mg/L of lead nitrate (Pb(NO3) 2 ) was administered to the fourth group (the combination group). According to the findings, when MPs and Pb were combined for 15 days, the red blood cells (RBCs), thrombocyte, and lymphocytes were significantly reduced in comparison to the control fish. When compared to the control fish, the fish exposed to MPs and Pb alone or together showed a significant rise in blood interleukin-1β (IL-1β) and interleukin-6 (IL-6) cytokines. Both MPs and Pb exposure in catfish resulted in significant change in the plasma electrolytes. The fish treated with MPs and Pb individually or in combination showed significant reduction in superoxide dismutase (SOD) and total antioxidant capacity (TAC) levels compared to the control group. The fish exposed to the combined action of MPs and Pb showed a considerable modification in all biochemical markers. The difference in the mean concentration of Pb (mg/l) between the fish exposed to Pb alone and the fish subjected to Pb and MPs combination was not statistically significant. In conclusion, according to this investigation, exposure to Pb caused an insignificant increase in Pb accumulation when MPs were present. However, co-exposure may result in anaemia, cellular harm, extremely high levels of oxidative stress, and an inflammatory reaction.